2021
DOI: 10.2109/jcersj2.21039
|View full text |Cite
|
Sign up to set email alerts
|

Defect chemistry in perovskite ferroelectrics—History, present status, and future prospects—

Abstract: Perovskite ferroelectrics such as BaTiO 3 and PbTiO 3 provide various functions arising from spontaneous polarization. Here, the history, present status, and future prospects of the defect chemistry for BaTiO 3 are described. Even for non-doped samples, unintentional impurities including Fe govern the defect chemistry and its related properties. By solving multiple nonlinear equations employing the thermodynamic data set reported, majority/minority defect-concentration diagrams are available not only in a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 216 publications
0
5
0
Order By: Relevance
“…gap-state engineering, can activate the visible-light PV response. The impact of chemical doping on the optical, [155][156][157][158][159][160] structural, 161,162) and electrical [163][164][165][166][167][168][169][170][171][172][173] properties of materials has been intensively studied by many researchers. Chemical doping of conventional ferroelectric oxides such as LiNbO 3 , 2,3,76) BaTiO 3 , 75,174,175) and Pb-based perovskites 85,87,176) effectively enhances the PV response.…”
Section: Gap-state Engineeringmentioning
confidence: 99%
“…gap-state engineering, can activate the visible-light PV response. The impact of chemical doping on the optical, [155][156][157][158][159][160] structural, 161,162) and electrical [163][164][165][166][167][168][169][170][171][172][173] properties of materials has been intensively studied by many researchers. Chemical doping of conventional ferroelectric oxides such as LiNbO 3 , 2,3,76) BaTiO 3 , 75,174,175) and Pb-based perovskites 85,87,176) effectively enhances the PV response.…”
Section: Gap-state Engineeringmentioning
confidence: 99%
“…Moreover, BiFeO 3 has a Curie temperature (T C ) of 830 °C, 47,48) which is much higher than that of PbTiO 3 (495 °C49) ) Barium titanate, BaTiO 3 , play an essential role for ceramic capacitor applications 50,51) and also for ferroelectricderived functions. [52][53][54][55][56] In tetragonal P4mm symmetry, Ti and Ba are displaced cooperatively along the polar c axis, leading to a P s of 26-29 μC cm −2 . 57,58) For (1−x) BiFeO 3 -x BaTiO 3 ceramics, structural analysis showed that an x increase changes a crystal symmetry from R3c rhombohedral to pseudo-cubic at ca.…”
Section: Introductionmentioning
confidence: 99%
“…9,10) Moreover, the polar lattice of BaTiO 3 gives rise to an unparalleled dielectric function that can be utilized for multilayer ceramic capacitors (MLCCs). 11,12) The widespread usage of MLCCs more or less relies on the defect chemistry [13][14][15][16][17][18][19][20][21] established for SrTiO 3 and BaTiO 3 . At present, intensive efforts [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] have been made to explore nanostructured materials and devices using BaTiO 3 -based materials, whereas the deep understanding of defects is far from complete for Pb(Zr, Ti)O 3 , [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] (Bi, Na)TiO 3 , …”
Section: Introductionmentioning
confidence: 99%
“…The well-established defect chemistry in BaTiO 3 17,19,98,99) enables us to develop a defect-induced function. Recently, we have proposed successive redox mediated PV effect that can activate visible-light response.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation